Status and distribution of selenium in selenium-enriched peanut sprouts - Mengqing Han; Kunlun Liu; Muhammad Tayyab Rashid; Guangsu Zhu; Yunshan Wei (Grain & Oil Science and Technology)
Selenium is one of the essential trace elements in human body, however, due to the limitation of geographic factors, the intake of selenium is seriously insufficient in most regions. In this study, selenium-enriched peanut sprouts with high selenium content were prepared by soaking peanut seeds in sodium selenite. The content and distribution of selenium in germinated peanuts were investigated. The results showed that 200 μmol/L sodium selenite and germination for 6 days resulted in the highest total selenium, organic selenium content, and organic selenium conversion in peanut sprouts. Selenium exists in peanut sprouts mainly in organic selenium form, of which selenoproteins are the most critical organic selenium carriers. ABTS free radical scavenging capacity and reducing power assays showed that alkali-soluble protein had the highest antioxidant activity among the four soluble proteins, attributed to its high selenium binding level. Radicle and cotyledons of peanut seedlings were significantly enriched with selenium compared to hypocotyl. Amino acid analysis and SDS-PAGE results showed that selenium increases significantly after peanut germination and selenium enrichment. This study provides a simple, environmentally friendly, and effective way of selenium enrichment and offers a theoretical basis for applying selenium-enriched foods in food and medicine.